Advising patients on visual fitness to drive: implications of revised DVLA regulations. Issue 4 (7th November 2014) - Latham, Keziah; Katsou, Maria Foteini; Rae, Sheila
Abstract : Aim: To examine the relationship between the two UK vision standards for driving: the ability to read a number-plate at 20 m and achieving 6/12 (+0.30 logMAR). Methods: 120 participants were assessed without refractive correction in this cross-sectional study. Vision was assessed with a Snellen chart, Early Treatment of Diabetic Retinopathy Study (ETDRS) style logMAR letter chart and logMAR chart using Landolt rings. Ability to read a post-2001 number-plate was assessed outdoors. Results: For all charts, there was an 'overlap zone' of visions within which it was uncertain whether participants would pass the number-plate test. Within this zone, sensitivity and specificity of the 6/12 cut-off for predicting number-plate performance were reasonable for Snellen and ETDRS style charts, but poor for Landolt. All participants with 6/7.5 Snellen (+0.10 logMAR ETDRS) or better could read a number-plate. Some participants (2–6%) with vision between this level and 6/12 could not read a number-plate, and 14%–15% could read a number-plate but not achieve 6/12. Conclusions: To best predict drivers' ability to read a number-plate, vision should be assessed using a logMAR letter chart or a Snellen chart scored by full line. Drivers with 6/7.5 (+0.10 logMAR) or better vision can be advised that they meet the driving standard. Drivers with acuity between 6/9 and 6/12 (+0.12—+0.30 logMAR) should be advised to check their ability to read a number-plate, as some may not be able to. Clinicians will see patients who can read a number-plate, but do not achieve 6/12, who will need improved vision to meet visual requirements for driving.